Pr-технології: сучасна специфіка комунікацій - Вертегел, Сергій Якович; Вертегел, Сергей Яковлевич; Vertehel, Serhii (My University, 2018)
UK: У статті розглянуто зв’язки з громадськістю як частини маркетингових комунікацій та визначення їх ефективності. Розкрито сутність та особливості сучасних моделей оцінки ефективності маркетингових комунікацій. Досліджено ефективність та розвиток сучасних PR-технологій в Україні, який відбувається на тлі становлення інформаційного суспільства. Здійснено оцінку ефективності перспективних засобів комунікаційної політики. Надано рекомендації щодо управління маркетинговими комунікаціями. EN: The growth of the role of marketing communications is due to the peculiarities of economic relations between market players. Effective marketing communication system is characterized by the use of various communication tools and the emergence of new tools of information influence. The purpose of the article is to study the essence of public relations as part of the marketing communications of the enterprise. Using PR-technologies to solve communication problems. The object of research is the process of using PR-technologies in marketing communications of the enterprise. Achievement of this goal is possible with the use of such a tool of marketing communications as public relations. The purpose of this article is to study the essence of public relations as part of the marketing communications of the enterprise and determine their effectiveness. Public relations as one of the main elements of marketing communications in many respects predetermines the competitiveness of enterprises, playing a prominent role in the formation of a marketing strategy.Marketing communications is the process of transferring information about an enterprise and its product in order to influence the target audience. Public Relations - Establishing relationships between the company and various contact audiences by creating an image that is beneficial for the company. The use of elements of a marketing communications complex is integrated. The development of marketing communications strategies and programs in creases the level of communication policy management efficiency. PR-technologies are complex. The influence of communicative technologies on the development of various spheres of human activity is increasing.
Pr-technologies: current specification of communications
Keywords: паблік рилейшнз; ефективність; маркетингові комунікації; управління маркетинговими комунікаціями; public relations; effectiveness; marketing communications; marketing communications management